Qualidade de vida no trabalho em auxiliares de loja de um supermercado em São Luís - FERREIRA, Ramon Pereira (2020)
The 50's were the milestone of studies in QWL, mainly regarding to worker satisfaction towards the organization and the task performed. The term Quality of Working Life (QWL) was introduced by Louis Davis, from UCLA, Los Angeles, in contribution to the Sociotechnical School, in the early 1970s. From that point, it was possible to notice that QWL relies itsroots in private and business field that, historically and gradually, has become more competitive and fundamental for the investigation researches, which seeks to understand the vision of this global worker. Therefore, it was observed in the literature an interrelation between People Management and Quality of Working Life: where an efficient and effective People proposes to investigate quality of life at work among store assistants, known as “baggers” of a Supermarket in São Luís - MA. It is a quantitative study mediated by a bibliographic and field research, with a descriptive and exploratory nature, aiming to investigate the perception of store assistants about QWL. Direct observation, field diary and photographic record have been used, as well as a questionnaire about quality of life at work based on the BPSO-96 model and treated statistical y by the “SPSS -version 20” software. The statistical analysis showed the importance of QWL actions in organizational environment, the actions to be taken immediately, as well as the possibilities of managing the working life quality of the researched public in an appropriate way, which is very necessary from the perspective of workers and researched organization. It has been clear that the challenges to raise awareness and implement working life quality programs are enourmous, starting with the difficulty in attract leadership for this sort of action. On the other hand, there was a clear support from the research participants and the other employees (repositories, security guards, general services, etc.), that weren’t included in the researched, that heard about the research and were hopeful that something could be changed, revealing a lack of this type of project in the company. Thisresearch was essential to enlighten my experience with teaching and research, showing me several positive paths and to solve some questions that practice revealed to me. Furthermore, this process of construction, execution and conclusion, brought even more identification with the possibilities of acting as a researcher and human resources professional, being clear that our practice can collaborate with a more just, equal and determinant society for significant changes in people's lives, as well as their work.